Van Allen Probes Observations of Oxygen Ions at the Geospace Plume - Foster, John C.; Erickson, Philip J. (Frontiers in Astronomy and Space Sciences, 2021)
The geospace plume couples the ionosphere, plasmasphere, and magnetosphere from sub-auroral regions to the magnetopause, on polar field lines, and into the magnetotail. We describe Van Allen Probes observations of ionospheric O+ ions at altitudes of 3 to 6 RE in the near vicinity of the geospace plume in the noon and post-noon sector. The temporal variation of warm ion fluxes observed as a function of time on a moving spacecraft is complicated by changing spacecraft position and complex ion drift paths and velocities that are highly sensitive to ion energy, pitch angle and L value. In the "notch" region of lower density plasma outside the morning-side plasmapause, bi-directionally field aligned fluxes of lower energy (<5 keV) ions, following corotation-dominated drift trajectories from the midnight sector, are excluded from geospace plume field lines as they are deflected sunward in the plume flow channel. In general, O+ at ring current energies (~10 keV) is bi-directionally field aligned on plume field lines, while lower energy O+ (< 3 keV) are absent. The observation of ion plumes with energies increasing from ~1 keV to > 20 keV in the dusk sector outer plasmasphere is interpreted as evidence for localized ionospheric O+ outflow at the outer edge of the geospace plume with subsequent O+ acceleration to > 50 keV in < 30 min during the ions' sunward drift.